Pengaruh Bladder Training terhadap Kemampuan Berkemih Pasien Stroke yang Terpasang Kateter di Rumah Sakit Royal Prima Medan - Br Barus, Sivitaria; Surabina, Helsa; Taufik, Taufik; Tywa N. Tambunan, Heryn; Nurhayati, Evalatifah (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Stroke is the second leading cause of disability and death in the world. This study aims to determine the effect of bladder training on the ability to urinate in stroke patients with catheters at the Royal Prima Hospital Medan. This type of research is quantitative with a quasi-experimental one group pretest-posttest design. The sampling technique used total sampling. The research instrument used an observation sheet containing information about the ability to urinate. Data were analyzed univariately and bivariately using the Wilcoxon test. The results of the analysis showed that there was an effect of bladder training on the ability to urinate in stroke patients with catheters at the Royal Prima Hospital Medan with a p value of 0.000. It is recommended that hospital management implement bladder training in stroke patients with catheters so that patients have the ability to urinate.